DFT calculations of vibrational frequencies of carbon-nitrogen clusters: Raman spectra of carbon nitrides - Rosli, A.N.; Zabidi, N.A.; Kassim, H.A.; Shrivastava, K.N. (Kluwer (now part of Springer), 2010)
We have performed the calculation of structures of clusters containing carbon and nitrogen atoms. We determine the bond lengths in each case. We also calculate the vibrational frequencies of all of the clusters. We compare the calculated values of the vibrational frequencies with those measured by the Raman spectra of amorphous carbon nitrides. Some of the calculated frequencies are in agreement with those measured. We identity that linear structures and hence ``back bones'' are present in the glassy state.